The Emerging Role of N-Acetylcysteine in Psychiatry: A Narrative Review of Available Data - Marazziti, Dona tella; Caruso, Valerio; Cappellato, Gabriele; Chiarantini, Ilaria; Gurrieri, Riccardo; Perrone, Paola; Violi, Miriam; Crivelli, Nicola Schulz Bizzozzero; Weiss, Francesco; Perugi, Giulio (Current Medicinal Chemistry, 2025)
N-acetylcysteine (NAC), a cysteine derivative with a reactive thiol group, possesses antioxidant and anti-inflammatory properties. Its redox activity plays a central role in scavenging reactive oxygen and nitrogen species and modulating cellular signaling pathways. Recent research highlights its potential role in psychiatric disorders through the modulation of oxidative stress and inflammatory pathways. This narrative review examines the efficacy of NAC in treating psychiatric conditions, including mood disorders, schizophrenia, anxiety disorders, post-traumatic stress disorder (PTSD), obsessive-compulsive disorder (OCD), substance use disorders (SUDs), and neurodevelopmental disorders. A comprehensive search of PubMed, Scopus, Embase, PsycINFO, and Google Scholar databases was conducted for studies published between March 1, 2007, and December 30, 2024. The search utilized keywords related to NAC and psychiatric disorders. Data were critically analyzed to evaluate NAC’s therapeutic potential. Preclinical studies demonstrate NAC’s benefits in reducing oxidative stress, inflammation, and modulating neurotransmitter systems. Animal models of depression, schizophrenia, and OCD show symptom reduction through glutamatergic and antioxidant mechanisms. Clinical trials reveal NAC’s efficacy as an adjunct in treating major depressive disorder, bipolar disorder, and schizophrenia, particularly for negative and cognitive symptoms. Evidence for anxiety disorders, PTSD, and OCD is limited but suggests anxiolytic and anti-obsessive effects. In SUDs, NAC shows promise in reducing cravings and substance-seeking behavior, while preliminary findings in autism suggest improvements in irritability and hyperactivity. NAC exhibits potential as an adjunctive treatment for various psychiatric disorders due to its safety profile, low cost, and broad mechanisms of action. However, clinical results are mixed, highlighting the need for larger, well-designed trials to confirm its efficacy and define optimal dosing strategies.
Keywords: psychiatric disorders